"Lungisa"—Weaving Relationships and Social Space to Restore Health in Rural KwaZulu Natal. (6th March 2014) - Wickström, Anette
<x xml:space="preserve">Abstract</x> Many Zulu people who live in big cities in South Africa return to their rural homestead when they fall ill. Although the health care offered in rural areas is not efficient, people wish to connect to their family and ancestors. My aim is to explore acts of lungisa ("to put in order") and what they say about health, agency, and the circumstances under which people live. Returning home means weaving oneself firmly within a web of relationships that are located in material things and places. Healing involves imperfect strategies used to better connect bodies, relationships, and places. I theorize the acts of returning using Adriana Cavarero's concept of weaving together and argue that people produce space and relationships over time to exert some control over a life lived under political and economic circumstances that have created separation. Six months of ethnographic fieldwork make up the material for my analysis.